Samal Reflexes of Proto-Austronesian Phonemes - Antworth, Evan L. (The Archive; Vol 4 (1984): Publication Four: Studies on Philippine Minor Languages, 2025)
The Sambal languages of the Philippines are a group of three closely related speech varieties, here referred to as Bolinao Sambal (Bl), Tina Sambal (Ti), and Botolan Sambal (Bt). Zorc 1977 groups Sambal with Ivatan, Kapampangan, and North Mangyan as the North Extension of the Southern Philippine branch of languages. However, he notes that Reid and McFarland have independently concluded that Sambal and Kapampangan are genetically Northern Philippine languages. Using a lexicostatistical method based on shared cognate percentages, Walton 1977 has places the Sambal languages in the Central Philippine branch of languages, which includes Kapampangan, Tagalog, Bikol, and Visayan. The uncertain genetic affiliation of the Sambal languages will not affect the analysis presented in this paper. I have adopted a deductive approach; I start with Proto-Austronesian (PAN) phonemes and ask what their reflexes are in the Sambal languages. Thus Proto-Sambal (PS) phonemes are reconstructed only when they can be traced back to Proto-Austronesian. I will make special note of splits and mergers, problems presented by the Sambal data, and any bearing the Sambal evidence has on current views of Proto-Austronesian and Proto-Philippine (PPh) phonology.